The use of Generative AI in qualitative analysis: Inductive thematic analysis with ChatGPT (Journal of Applied Learning and Teaching, 2024)
This article describes a methodological innovation in the analysis of qualitative data using Generative AI (GenAI) tools alongside traditional research methodologies to conduct inductive thematic analysis. The case study employs an integrative method that comprises two researchers conducting simultaneous analysis: one using manual and traditional research approaches to coding, analysis, and interpretation, and the other conducting the same analysis but with the support and assistance of GenAI tools, namely, the premium version of ChatGPT (GPT-4).The key strengths of this approach include the enhanced capacity for data processing and theme identification offered by GenAI, along with the nuanced understanding and interpretative depth provided by human analysis. This synergy allows for a richer and more complex understanding of the themes present in the data. The challenges encountered include managing the inconsistencies and hallucinations of GenAI outputs and the necessity for rigorous validation processes to maintain research validity. The findings indicate a complementary relationship between GenAI and human researchers, where the use of such tools can expedite the analytical process without diminishing the essential role of the researcher’s expertise and critical engagement.